Gestão escolar: a prática pedagógica administrativa na política de educação inclusiva - Tezani, Thaís Cristina Rodrigues [UNESP] (My University, 2010)
The paper presents the results of a doctoral dissertation that covered the analysis of knowledge involving the everyday teaching and administrative practices of school managers who worked with the proposed construction of a citywide system of inclusive e ducation, while an educational policy. The aim was to follow the school management towards the proposed inclusive educationin three elementary schools in a medium-sized city in the state of São Paulo. The data were collected at the earlier school, a middle-aged one and another recently opened. The stages of the study were: 1) review of literature on: a) qualitative ethnographic research applied to education, b) principles of autonomy, planning, decentralization, c) the education of the school manager and d) relationship between school management and inclusive school; 2) data collection in schools, 3) description and categorization of data and 4) analysis and interpretation of results. To develop the methodology were used observations of the participants, semi-structured interviews, analysis of official documents of the school (internal and external). It was concluded that there is a lack of political-pedagogical project collectively built, a difficulty in developing coordinated actions aimed at the realitiy, problems in interpersonal relationships; a gap gulf between the proposed policy, the discourse about it and the daily practice. The school management is responsible for the construction of an inclusive school, but in the reality studied it was directed at administrative issues at the expense of the pedagogic ones.

Este trabalho apresenta os resultados de uma tese de doutorado que teve como tema a análise dos saberes que envolvem a prática pedagógica e administrativa cotidiana de gestores escolares que atuaram com a proposta de construção de um sistema municipal de educação inclusiva, enquanto política educacional. Seu objetivo foi acompanhar a trajetória da gestão escolar diante da proposta de educação inclusiva em três escolas do ensino fundamental de uma cidade de porte médio do interior do Estado de São Paulo. Realizou-se a coleta de dados na escola mais antiga, uma de idade intermediária e outra recém-inaugurada. As etapas do trabalho foram: 1) revisão de literatura sobre: a) pesquisa qualitativa do tipo etnográfico aplicada à educação; b) princípios de autonomia, planejamento, descentralização; c) formação do gestor escolar e d) relação entre gestão escolar e a escola inclusiva; 2) coleta de dados nas escolas; 3) descrição e categorização dos dados e 4) análise e interpretação dos resultados. Para o desenvolvimento da metodologia, foram utilizadas observações dos participantes, entrevistas semiestruturadas, análise dos documentos oficiais das escolas (internos e externos). Concluiu-se que há inexistência de projeto político-pedagógico construído coletivamente; dificuldade no desenvolvimento de ações coordenadas e adaptadas às realidades; problemas de relacionamento interpessoal; fosso entre a proposta política, o discurso e a prática pedagógica cotidiana. A gestão escolar é uma das responsáveis pela construção da escola inclusiva, mas, na realidade estudada, estava direcionada para questões administrativas em detrimento das pedagógicas.
School management: the pedagogical practice in the administrative policy of inclusive education
Keywords: Public education policy; School management; Ethnography; Política pública educacional; Gestão escolar; Etnografia